Wind turbines and bat mortality: interactions of bat echolocation pulses with moving turbine rotor blades. - Chloe V. Long; James A. Flint; Paul Lepper; S.A. Dible (2009)
Wind power is a rapidly growing energy technology, popular for being a clean, reliable and cost-efficient renewable energy source. However, recently concern has been growing over the impact of wind turbines on flying wildlife, with both birds and bats found dead around turbine bases and observed collisions with moving turbine rotors. This phenomenon is widespread and has received enough attention to warrant investigation into how and why these collisions occur. In this paper we investigate the acoustic interaction of bats with wind turbines, in particular the interpretation of reflected sound pulses (echolocation) used by bats to navigate. This paper focuses on the effects of moving turbine rotor blades on reflected acoustic pulses, analogous to what might be presented to an echolocating bat approaching an operational turbine at rotor height. High frequency, simulated FM bat pulses were used to assess reflected echo properties from microturbines (experimentally and in simulation) in order to investigate what interaction rotor movements had with incoming pulses and the potential consequences for an echolocating bat near a moving wind turbine.